Asian Tigers, African Lions : Comparing the Development Performance of Southeast Asia and Africa. - Berendsen, Bernard (African dynamics., 2013)
Asian Tigers, African Lions is an anthology of contributions by scholars and (former) diplomats related to the 'Tracking Development' research project, funded by the Netherlands Ministry of Foreign Affairs, and coordinated by the African Studies Centre and KITLV, both in Leiden, in collaboration with scholars based in Africa and Asia. The project compared the performance of growth and development of four pairs of countries in Southeast Asia and Sub-Sahara Africa during the last sixty years. It tried to answer the question how two regions with comparable levels of income per capita in the 1950s.